KAJIAN YURIDIS PENANAMAN MODAL ASING YANG MEMPEKERJAKAN TENAGA KERJA ASING BERDASARKAN HUKUM KETENAGAKERJAAN DI INDONESIA - Umboh, Karel Yossi; Friend Henry Anis; Ollij Anneke Kereh (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2023)
This research was carried out with the aim of knowing and analyzing the legal regulations for foreign investment employing foreign workers in Indonesia and the application of the law regarding the use of foreign workers in North Sulawesi. The method used in this research is a normative legal research method which uses a statutory approach to study the legal regulation of foreign workers and an empirical method to determine the application of foreign labor laws. The research results show that the regulation of foreign workers in Indonesia is contained in Law No. 13 of 2003 concerning Employment and its derivative regulations and is also contained in the Job Creation Law as regulated in Law No. 6 of 2023. In the Employment Law, provisions for foreign workers are contained in Article 42 to 45. Several provisions regulate that every employer who employs foreign workers is required to have written permission from the Minister or appointed official. Foreign workers can be employed in Indonesia only in an employment relationship for certain positions and certain times. The implementation of the law regarding the use of foreign workers in North Sulawesi is carried out by several agencies, namely those at the center, in this case the Ministry of Manpower, as well as agencies in the regions, namely the Manpower Service and the Immigration Office..